A new tooth brushing approach supported by an innovative hybrid toothbrush-compared reduction of dental plaque after a single use versus an oscillating-rotating powered toothbrush - D. Klonowicz; M. Czerwinska; A. Sirvent; J-Ph. Gatignol (BMC, 2018)
Abstract Background An innovative hybrid toothbrush was designed functioning either in manual mode, in powered mode (sonic) or in combined mode (manual and powered). The primary aim of this study was to evaluate and compare the clinical efficacy of this first hybrid toothbrush (Elgydium Clinic/Inava Hybrid) used in combined mode to a marketed oscillating-rotating powered toothbrush (Oral-B Vitality) in the reduction of dental plaque after a single use. The secondary aims were to evaluate the tolerance and acceptability of each device. Methods It was a randomized, examiner-blind, single-center study performed on two parallel groups: hybrid toothbrush (n = 33) versus oscillating-rotating toothbrush (n = 33). A brushing exercise was conducted for two minutes on subjects presenting a "Silness and Löe Plaque Index" (PI) between 1.0 and 2.0 and a "Modified Gingival Index" between 1.0 and 2.0. They were not to have ever used an electric toothbrush. To assess the device effect after brushing, a paired t-test was applied on the change outcome (After-Before brushing). An unpaired t-test was used to compare the efficacy of both devices. A global tolerance assessment of each powered toothbrush was done on all the subjects. The number and percentage of reactions related to each toothbrush was collected and the final tolerance assessment was estimated. Results After a single use, the hybrid toothbrush used in combined mode presented a global anti-plaque efficacy characterized by a significant decrease of the global PI of 45% on average (p < 0.0001; paired t-test). It was as effective as the oscillating rotating toothbrush in plaque removal (p > 0.05; unpaired t-test). The global tolerance of both toothbrushes was judged as "Good" and they were equally appreciated by the users. Conclusion The results of this one-time use trial demonstrate the efficacy of the hybrid toothbrush used in combined mode for plaque removal. The hybrid toothbrush design allows each user to adapt tooth brushing to his preference (manual / sonic / combined), his skills or his mouth condition. We hypothesize that such an individualized approach can favor long term compliance with oral health recommendations and improve global oral wellness. Trial Registration ISRCTN12394494, 20/02/2018 - Retrospectively registered.